Die stoetmeester van Etienne van Heerden: gesigte van ’n gestorwe siener - M. Hattingh (Literator, 1995)
Etienne van Heerden’s Die stoetmeester: visions of a dead prophet Although the title indicates that Van Heerden's fourth novel tells the story of a stud-master, the narrative structure shows how one personal history implicates a variety of other stories. In this way the novel illustrates how subjectivity interacts with the narratives of history and of culture. The dominant focalizer in the novel is a deceased Afrikaner attorney, Siener (meaning prophet), who is reviewing the circumstances leading to his death. His exceptional narrative position entitles him to go back in time and enter the thoughts of all the characters involved. The result is a polyphonic display of voices and stories. In this article the question is posed whether the narrative position of the novel as a post-modern critique of truths and certainties can be reconciled with Siener’s explicit display of political preferences. Ultimately Van Heerden’s novel illustrates the Afrikaner author’s struggle for moral authority in the present transitional era.